2022
DOI: 10.3390/foods11213420
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Sales of Suboptimal Foods with Sustainability and Authenticity Marketing Strategies

Abstract: To reduce food waste, it is essential to motivate consumers to purchase and consume products that deviate from optimality on the basis of only cosmetic specifications (also called suboptimal products). Previous research has shown it to be challenging to motivate consumers to buy such suboptimal products. Sustainability or authenticity positioning of suboptimal products may be a promising avenue, but no research to date has examined their effects on consumer behaviour. The current research examines whether sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Indeed, van Giesen and de Hooge (2019) and Wang et al (2022) found that communicating the naturalness of imperfect fruits (via a label) can increase consumer WTP as much as a price discount can. In a recent field experiment with oddly shaped pears and cucumbers, de Hooge et al (2022) found that sustainability and authenticity messages can not only increase the perceived similarity between suboptimal and optimal products, but also the actual sales. Qi et al (2022) found that dual messages which emphasise the reduction of food waste as well as naturalness and authenticity of the imperfect products, increased WTP significantly (Qi et al, 2022).…”
Section: State Of Researchmentioning
confidence: 99%
“…Indeed, van Giesen and de Hooge (2019) and Wang et al (2022) found that communicating the naturalness of imperfect fruits (via a label) can increase consumer WTP as much as a price discount can. In a recent field experiment with oddly shaped pears and cucumbers, de Hooge et al (2022) found that sustainability and authenticity messages can not only increase the perceived similarity between suboptimal and optimal products, but also the actual sales. Qi et al (2022) found that dual messages which emphasise the reduction of food waste as well as naturalness and authenticity of the imperfect products, increased WTP significantly (Qi et al, 2022).…”
Section: State Of Researchmentioning
confidence: 99%
“…Understanding the motivations behind consumers' decisions to purchase and consume imperfect produce presents a promising approach to combating food waste, with potential benefits spanning various levels of the food supply chain [50]. However, the specific factors influencing the choice to purchase or avoid "ugly" products remain somewhat unclear [51].…”
Section: Introductionmentioning
confidence: 99%